PENGARUH BRAND PERFORMANCE THE JAYAKARTA BANDUNG BOUTIQUE SUITE HOTEL & SPA TERHADAP KEPUTUSAN TAMU UNTUK MENGINAP - Agustiani, Indah Nur; Barbo, Anthony (Universitas Pendidikan Indonesia, 2012)
The impact of hotel industries which is developing the high competition of hotel industries. The level of room residential is the important thing to view that the number of the room is sold. The guest decision to stay is the most important thing to the hotel industries. With the guest decision to hotel, then the level of guest residential will increase which is the main target of hotel industries. Therefore the Jayakarta Bandung Boutique Suite Hotel Spa wants the guest decision to be enhanced. The one of effort to increase the guest decision to stay is maximize the brand performance which is do it by The Jayakarta Bandung Boutique Suite Hotel and Spa. The purpose of the study is to obtain findings the brand performance which has been done, the decision to stay in The Jayakarta Bandung Boutique Suite Hotel Spa and the influence of brand performance towards the decision to stay. Kevin L. Keller is the theory of brand performance which is used. While the theory of post-visit behavior using the theory of Kotler and Keller. The object of the study is the visitor who stay in The Jayakarta Bandung Boutique Suite Hotel Spa. This type of research is descriptive and verification, and the method used is explanatory survey stratified random sampling, hence obtained a population of 100 respondent. The data analysis technique and hypothesis test used is the path analysis (path analysis). The results show interesting findings, that the brand performace give the significant influence towards to the stay decision which consist of product, brand, reservation channel, lenght of stay,the number of room reservation and the payment method. The biggest impact of brand performance towards the stay decision is obtained from Product Reliability, Durability and Service Ability and the smallest influence is obtained from Service Effectiveness, Efficiency, And Empathy. As for suggestions for the company in improving the decision to stay at The Jayakarta Bandung Suite Boutique Hotel Spa is a brand performance through the development of a more exciting, creative, innovative, effective and efficient.